NEGARA DAN MODERNISASI PENDIDIKAN ISLAM DI INDONESIA - Eka Sri wahyuni; Anik Huzaimah (Universitas 17 Agustus 1945 Semarang, 2022)
The existence of the SKB of three ministers of social, economic, political, cultural and national civilization and for Muslims the three ministerial SKB has meaning, first, the occurrence of social and vertical mobility of madrasa students which so far has been limited to traditional educational institutions (madrasas and Islamic boarding schools), and secondly, opening up opportunities for the possibility of santri children entering the area of ​​work in the modern sector. The existence of Islamic education policies during the New Order era brought changes to Islamic education and the life of the nation, especially Muslims. The birth of a three-ministerial SKB stating that madrasah alumni could continue their education in public schools both at home and abroad. And that was born from the process of modernizing Islamic education which began in the early 20th century. In line with the development of social and economic institutions, the Muslim modern elite mostly live in cities, are highly educated, have religious knowledge, work in the New Order bureaucracy and in various secular modern institutions, the social and religious position of the modern Muslim elite makes them have social access. and strong politics. And they spread a lot to membership in the DPR both through Islamic and nationalist parties such as Golkar and others.